The Philosophical Values of Islamic Inheritance Law - Ismail Ismail (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
Abstract: The law of inheritance has been determined very clearly in the Qur’an and this provision has also been established as a qathi' or final legal basis by jumhur or majority ulama. However, in reality, there are still criticisms of the inheritance law provisions. This article aims to further examine the issue of qat'hi and zhanni (the final one and the need intrepretation) related to inheritance and how the philosophical values ​​of inheritance law in Islam. The philosophical study referred to in this article is related to the purpose of syara’ to determine the distribution of inheritance in such a way and what philosophical basis and values ​​are used. This article also describes the share of men and women with one to two balances. This article is based on literature study by using textual sources, namely the text of the Qur’an (especially verses on the law of inheritance) as the main reference in the reconstruction of philosophical thinking in Islamic inheritance law. The analysis technique in this research is descriptive analysis. So, the philosophical basis and the purpose of inheritance law in Islam is an effort to realize justice in order to achieve mutual benefit for the heirs. However, if a change is needed regarding inheritance law that is relevant to the conditions and situation at the time of the inheritance law decision, there is no harm in providing additional law. Keywords: Philosophical values, inheritance law, Islam. Abstrak: Hukum waris telah ditentukan dengan sangat jelas dalam Alquran serta ketentuan tersebut juga telah ditetapkan sebagai dasar hukum yang qathi’ oleh jumhur ulama. Akan tetapi realita yang terjadi masih ada kritik terhadap ketentuan hukum waris tersebut. Artikel ini bertujuan mengkaji lebih jauh masalah qat’hi dan zhanni-nya terkait waris dan bagaimana nilai-nilai filosofis hukum kewarisan dalam Islam. Kajian filosofis yang dimaksud dalam artikel ini terkait tentang tujuan syara' menetapkan pembagian warisan sedemikian rupa dan apa dasar dan nilai filosofis yang digunakan. Artikel ini juga menjelaskan tentang bagian laki-laki dan perempuan dengan perimbangan satu banding dua. Artikel ini berbasis penelitian pustaka dengan menjadikan sumber-sumber tekstual yakni teks Alquran (khusus ayat-ayat tentang hukum kewarisan) sebagai acuan utama dalam rekonstruksi pemikiran filosofis dalam hukum waris Islam. Teknik analisis dalam penelitian ini menggunakan Teknik analisis deskriptif. Jadi, dasar filosofis dan tujuan hukum waris dalam Islam merupakan suatu upaya untuk mewujudkan keadilan agar tercapai kemashlahatan bersama bagi ahli waris. Namun jika diperlukan sebuah perubahan terkait hukum kewarisan yang relevan dengan kondisi dan situasi pada saat keputusan hukum kewarisan tersebut maka tidak ada salahnya memberikan hukum tambahan. Kata-kata kunci: Nilai-nilai filosofis, hukum kewarisan, Islam.